2017
DOI: 10.1590/1982-0224-20160061
|View full text |Cite
|
Sign up to set email alerts
|

The role of Lithodoras dorsalis (Siluriformes: Doradidae) as seed disperser in Eastern Amazon

Abstract: Ichthyochory is an important process responsible for the high diversity of plant species in tropical flooded forests. Thus, this study aimed to investigate the role of a catfish species, Lithodoras dorsalis, as seed disperser in the flooded forests at the Amazon River mouth, Brazil. Analyzing the stomach contents of 371 individuals of Lithodoras dorsalis, the Germination Potential (GP%) and Germination Speed Index (GSI) of seeds that were removed intact were investigated. This allowed us to evaluate the germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This influence can be positive when fruit processing in the gut favours germination, for example due to the breakage of seed dormancy and facilitation of germination, or negative when seeds are destroyed as a result of harsh or long gut treatment (Torres, Castaño & Carranza-Quiceno, 2020). Whether seeds benefit from gut treatment or not also depends on specific traits of seeds such as seed size and hardness (Verdú & (Liu, Platt & Borg, 2004;Caputo & Vogt, 2008) and fish (S orio, Damasceno-Junior & Parolin, 2015; Barbosa & Montag, 2017). Our review shows that seeds of more than 30 palm species have been reported to benefit from gut treatment that involves seed defecation.…”
Section: (B) Gut Treatmentmentioning
confidence: 83%
See 2 more Smart Citations
“…This influence can be positive when fruit processing in the gut favours germination, for example due to the breakage of seed dormancy and facilitation of germination, or negative when seeds are destroyed as a result of harsh or long gut treatment (Torres, Castaño & Carranza-Quiceno, 2020). Whether seeds benefit from gut treatment or not also depends on specific traits of seeds such as seed size and hardness (Verdú & (Liu, Platt & Borg, 2004;Caputo & Vogt, 2008) and fish (S orio, Damasceno-Junior & Parolin, 2015; Barbosa & Montag, 2017). Our review shows that seeds of more than 30 palm species have been reported to benefit from gut treatment that involves seed defecation.…”
Section: (B) Gut Treatmentmentioning
confidence: 83%
“…Viable palm seeds have also been reported inside stomachs or in the dung of ungulates (e.g. Beck, 2006; Bodmer & Ward, 2006; Barcelos et al ., 2013), carnivores (Kays, 1999; Campos et al ., 2012), birds (Pizo & Simão, 2001; Cárdenas, Echeverry‐Galvis & Stevenson, 2021), primates (Stevenson & Link, 2010; Chaves, Stoner & Arroyo‐Rodríguez, 2012), turtles (Liu, Platt & Borg, 2004; Caputo & Vogt, 2008) and fish (Sório, Damasceno‐Junior & Parolin, 2015; Barbosa & Montag, 2017). Our review shows that seeds of more than 30 palm species have been reported to benefit from gut treatment that involves seed defecation.…”
Section: Interaction Outcomes In Palm–frugivore Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, most of tree species refers to those with primary seed-dispersal by vertebrates (i.e., gut-dispersal), although some species bear seeds that might be able to float; i.e., secondarily dispersed by water (Parolin et al, 2013(Parolin et al, , 2004. Others may be dispersed by mammal/birds and fishes (i.e., ichthyochory), particularly those species small seeds (Anderson et al, 2011(Anderson et al, , 2009, while others exhibit devices directly associated to hydrochory such as air-containing or spongy tissues (Barbosa & Montag, 2017;Wittmann et al, 2007). In both habitats (i.e., estuarine and floodplain forests), species bearing medium-sized (<1.5 cm length) and relatively light seeds (<2 g) predominate (Parolin, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This fact is corroborated by the presence in juvenile catches of B. filamentosum and C. undecimalis. These species are commonly found entering the estuaries, when salt variations are favorable, usually during periods of low rainfall [39,41] , seed dispersal species are more common during the rainy season, for example the species Lithodoras dorsalis which was collected in this study [42] . It was possible to observe during this study that the high presence of mangrove trees (e.g., A. germinans) and typical lowland percussion vegetation (e.g., Machaerium lunatum), showed high divergence in relation to habitats with less vegetation.…”
Section: Discussionmentioning
confidence: 99%